Desmin Phosphorylation Triggers Preamyloid Oligomers Formation and Myocyte Dysfunction in Acquired Heart Failure. Issue 10 (11th May 2018) - Rainer, Peter P.; Dong, Peihong; Sorge, Matteo; Fert-Bober, Justyna; Holewinski, Ronald J.; Wang, Yuchuan; Foss, Catherine A.; An, Steven S.; Baracca, Alessandra; Solaini, Giancarlo; Glabe, Charles G.; Pomper, Martin G.; et al.
Abstract : Rationale: : Disrupted proteostasis is one major pathological trait that heart failure (HF) shares with other organ proteinopathies, such as Alzheimer and Parkinson diseases. Yet, differently from the latter, whether and how cardiac preamyloid oligomers (PAOs) develop in acquired forms of HF is unclear. Objective: : We previously reported a rise in monophosphorylated, aggregate-prone desmin in canine and human HF. We now tested whether monophosphorylated desmin acts as the seed nucleating PAOs formation and determined whether positron emission tomography is able to detect myocardial PAOs in nongenetic HF. Methods and Results: : Here, we first show that toxic cardiac PAOs accumulate in the myocardium of mice subjected to transverse aortic constriction and that PAOs comigrate with the cytoskeletal protein desmin in this well-established model of acquired HF. We confirm this evidence in cardiac extracts from human ischemic and nonischemic HF. We also demonstrate that Ser31 phosphorylated desmin aggregates extensively in cultured cardiomyocytes. Lastly, we were able to detect the in vivo accumulation of cardiac PAOs using positron emission tomography for the first time in acquired HF. Conclusions: : Ser31 phosphorylated desmin is a likely candidate seed for the nucleation process leading to cardiac PAOs deposition. Desmin post-translational processing and misfolding constitute a new, attractive avenue for the diagnosis and treatment of the cardiac accumulation of toxic PAOs that can now be measured by positron emission tomography in acquired HF. Abstract : Supplemental Digital Content is available in the text.